Innovative approaches in reducing the cost of living among B40 group: The transportation policy perspective / Mohd Rozaimy Ridzuan and Noor Amira Syazwani Abd Rahman - Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani (Universiti Teknologi MARA Cawangan Pahang, 2021)
In Malaysia, the rate of income growth is lower than the price increase. This income inequality contributes to the cost of living in Malaysia. In the 2014 Household Spending Survey, the three most important components of household spending are housing, food and transportation. With this rising cost of living and declining growth rate, it is surmised that low income groups, particularly those with large families in urban areas, feel the pinch. Therefore, this study explored the recent efforts of the Malaysian government through its Ministry of Transportation in reducing the cost of living among B40 group. This study employed a qualitative study where content analysis had been carried out in order to analyse efforts taken by the Ministry of Transportation in reducing the cost of living among B40 group. This study delineated four programs introduced by the Ministry of Transportation in addressing the cost of living among B40 group. It is hoped that the present study would be able to supplement the information to the existing body of knowledge with regard to efforts in mitigating the burden of the cost of living faced by B40 group.